Itonama o Sihnipadara, lengua no clasificada de la Amazonia boliviana - Mily Crevels (Estudios de Lingüística, 2002)
The purpose of this paper is to give a preliminary sketch of some interesting structural features of Itonama, a moribund indigenous language spoken in Amazonian Bolivia, against the historic and sociolinguistic background of the area. Greenberg’s (1987) classification of Itonama as Paezan, a subbranch of Macro-Chibchan, has not been supported by other linguists and the language is still considered to be an isolate or rather an unclassified language. Itonama is a head-marking VSO language, which marks gender on the verb and distinguishes masculine and feminine gender in pronouns and demonstratives. It has a multiple classifier system and only two open word classes: verbs and nouns. While its nominal morphology seems quite transparent, the verbal morphology is much more complex with various prefix and suffix slots, verbal classifiers —which also appear on demonstratives—, body-part incorporation, and verbal number.